Gut Microbiota in NSAID Enteropathy: New Insights From Inside - Wang, Xianglu; Tang, Qiang; Hou, Huiqin; Zhang, Wanru; Li, Mengfan; Chen, Danfeng; Gu, Yu; Wang, Bangmao; Hou, Jingli; Liu, Yangping; Cao, Hailong (Frontiers in Cellular and Infection Microbiology, 2021)
As a class of the commonly used drugs in clinical practice, non-steroidal anti-inflammatory drugs (NSAIDs) can cause a series of adverse events including gastrointestinal injuries. Besides upper gastrointestinal injuries, NSAID enteropathy also attracts attention with the introduction of capsule endoscopy and double balloon enteroscopy. However, the pathogenesis of NSAID enteropathy remains to be entirely clarified. Growing evidence from basic and clinical studies presents that gut microbiota is a critical factor in NSAID enteropathy progress. We have reviewed the recent data about the interplay between gut microbiota dysbiosis and NSAID enteropathy. The chronic medication of NSAIDs could change the composition of the intestinal bacteria and aggravate bile acids cytotoxicity. Meanwhile, NSAIDs impair the intestinal barrier by inhibiting cyclooxygenase and destroying mitochondria. Subsequently, intestinal bacteria translocate into the mucosa, and then lipopolysaccharide released from gut microbiota combines to Toll-like receptor 4 and induce excessive production of nitric oxide and pro-inflammatory cytokines. Intestinal injuries present in the condition of intestinal inflammation and oxidative stress. In this paper, we also have reviewed the possible strategies of regulating gut microbiota for the management of NSAID enteropathy, including antibiotics, probiotics, prebiotics, mucosal protective agents, and fecal microbiota transplant, and we emphasized the adverse effects of proton pump inhibitors on NSAID enteropathy. Therefore, this review will provide new insights into a better understanding of gut microbiota in NSAID enteropathy.